Sensitive Determination of Sertraline in Commercial Drugs and Its Stability Check in Simulated Gastric Juice - Kocoglu, Elif Seda; Bakirdere, Sezgin; Keyf, Seyfullah (AOAC INT, 2016)
A sensitive analytical method was developed for the determination of sertraline in commercial drug samples by using GC MS. The selected-ion monitoring mode was used at the most sensitive m/z 274 to obtain a lower detection limit. LOD/LOQ values were obtained as 1.6/5.4 ng/mL for sertraline under the optimum conditions. The calibration plot was linear between 5.0 and 2000 ng/mL with the correlation coefficient of 0.9999. The validated method was successfully applied to three different brands of drug samples for both qualitative and quantitative measurement of sertraline. In this experiment, four replicate extractions were performed for each brand, and the results were compared to the values written on the labels of the drug brands. Spiking experiments were also performed to check the effect of the matrixes on the determination, and it was observed that there was no shift in the retention time of the analyte. In addition, simulated gastric juice experiments were performed to check the stability of sertraline in the stomach for 240 min, and it was observed that there was no change in the structure of the analyte.
Keywords: CHROMATOGRAPHY-MASS SPECTROMETRY; HUMAN PLASMA; LIQUID-CHROMATOGRAPHY; DESMETHYL-SERTRALINE; VALIDATION; METABOLITE; BLOOD; MS/MS; Chemistry; Food Science & Technology